2nd Order Sigma Delta Modulator Design using Delta Sigma Toolbox - Beigh, Nadeem Tariq; Prince Nagar; Hamid, Aamir Bin; Beigh, Faizan Tariq; Ahmad, Faroze (Asian Journal of Electrical Sciences, 2018)
This paper discusses the block level design of 2nd order sigma delta using the Delta Sigma Toolbox and Simulink .An optimized modulator is designed with scaled coefficients, giving a low power, low frequency and high OSR modulator. The modulator presented has an OSR of 256, bandwidth of 200Hz, SNR of 100dB, SNDR of 96 dB, ENOB of 16 bits (approx.).The designed modulator is ideal for low power and low frequency applications, as in case of conversion of brain wave signals which are in the frequency range of 10-100Hz.This work provides the baseline for the design of the same modulator using switched capacitor in CMOS technology of 0.18μm TMSC CMOS technology with VDD of 1.8V.The coefficient values a, b, g, c are the ratios of capacitors in switched capacitor level design.